2017
DOI: 10.1002/2016gl072355
|View full text |Cite
|
Sign up to set email alerts
|

Role of internal variability in recent decadal to multidecadal tropical Pacific climate changes

Abstract: While the Earth's surface has considerably warmed over the past two decades, the tropical Pacific has featured a cooling of sea surface temperatures in its eastern and central parts, which went along with an unprecedented strengthening of the equatorial trade winds, the surface component of the Pacific Walker Circulation (PWC). Previous studies show that this decadal trend in the trade winds is generally beyond the range of decadal trends simulated by climate models when forced by historical radiative forcing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…1). This may not happen due solely to an extreme internal fluctuation at interdecadal time scales 6 . However, additional analyses show that the failure to reproduce the observed trend only spans over the recent two decades, but not the entire 60-year period ( Supplementary Figs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). This may not happen due solely to an extreme internal fluctuation at interdecadal time scales 6 . However, additional analyses show that the failure to reproduce the observed trend only spans over the recent two decades, but not the entire 60-year period ( Supplementary Figs.…”
mentioning
confidence: 99%
“…1), consistent with a strengthening of the Walker circulation as suggested from atmospheric data 21 . There exist observational uncertainty 22 and a dependence of the trend magnitude on chosen period 6 , but the discrepancy between observations and climate models is obvious and critical not only for assessing the reliability of future climate changes in models but also for estimating the Earth's climate sensitivity (ECS) from historical records. Recent studies show that cloud and lapse rate feedbacks to doubling of CO2 concentration depend on spatial inhomogeneity in sea surface warming 8,9,23 , called the 'pattern effect' 24 .…”
mentioning
confidence: 99%
“…It has further been suggested that anthropogenic aerosols play a role during the 'global warming hiatus' by altering the trade winds and the state of the PDO (Smith et al 2016;Takahashi and Watanabe 2016), but the robustness of these results has been questioned (Kuntz and Schrag 2016;Oudar et al 2018). Further, observational uncertainties exist, and these are particularly large in the pre-satellite era (Bordbar et al 2017;Kajtar et al 2018). Reanalyses have been argued to overestimate the intensification of the Pacific Walker circulation during the past decades when compared to satellite-derived estimates (Chung et al 2019), but de Boisséson et al (2014 found the tropical Pacific trade wind trends, which are the surface expression of the Walker circulation cell, to be robust in different observations including reanalyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, other observational SST data sets and some reanalysis products show warming trend with La Niña‐like zonal structure during the instrumental period (Karnauskas et al, ) and a strengthening of the Walker circulation over the past several decades (Chung et al, ; Sohn et al, ). Due to strong natural variability, these trends are sensitive to the time period considered, and there is uncertainty in determining long‐term trends from observations (Bordbar et al, ). Nevertheless, there is a physically consistent hypothesis to explain suppressed warming in the eastern equatorial Pacific and the associated strengthening of the Walker circulation in response to increasing greenhouse gases (GHGs): an ocean dynamic thermostat mechanism (Clement et al, ).…”
Section: Introductionmentioning
confidence: 99%